ANALISIS BENTUK DAN MAKNA SYAIR LAGU GEREJA KRISTEN DALAM BUKU NYANYIAN PUJIAN DI GEREJA BAPTIS INDONESIA WANAMUKTI SEMARANG - Saputra, Oktavian Harys (Jurnal Seni Musik, 2016)
The researcher wants to know about the form and purpose of the ryhme of those songs that still being used at GBI Wanamukti, the problem formulation of this research are : (1). what type of song structure analysis of The Book of Nyanyian Pujian that is still being used at GBI Wanamukti Semarang? (2). what is the meaning that lies behind the rhyme in The Book of Nyanyian Pujian that is still being used at GBI Wanamukti Semarang?. The researcher used Qualitative Descriptive as the research method. The result of this research aim to know that "Jangan Aku Dilalu" NP 129, "Berkati Persembahanku" NP 359, "Bapa, Antarlah Kami" NP 360 are the songs that often being used at GBI Wanamukti Semaarang. "Jangan Aku Dilalui" NP 129 is a song with 2-piece structured pattern A (a a') and B (a b'). "Berkati Persembahanku" NP 359 has 1-piece with pattern A(a a'). "Bapa, Antarlah Kami" has 1-piece with pattern A (a a'). The meaning of the song "Jangan Aku Dilalui" NP 129 is about request to God to hear the church prayers as well as the recognition of God as the only hope of giving relief to the church. The meaning of "Berkati Persembahanku" song NP 359 is about regarding the request to God to bless the offering made for the church, as well as an acknowledgment that God is the main factor determining the success of the community. The song "Bapa, Antarlah Kami" NP 360 has the meaning of a request to the Lord to be with the congregation as they finished worship and will return to their respective homes.